BAGAIMANAKAH RESPON MASYARAKAT TERHADAP PERUBAHAN SKEMA BANTUAN SOSIAL PROGRAM KELUARGA HARAPAN (PKH) PADA MASA PANDEMI COVID-19 - Aris Tristanto; Yunilisiah; Tamrin Bangsu (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2022)
The purpose of this study is to provide an overview of the response of KPM PKH Nagari Gunuang Rajo on changes to the PKH assistance scheme issued by the government during the COVID-19 pandemic. This study uses a quantitative approach. The population in this study was KPM PKH in Nagari Gunuang Rajo with a sample of 125 people based on the sampling method developed by Isaac and Michael. Sampling was done by non-probability method, namely convention sampling. The data analysis technique used in this research is descriptive statistics. The results showed that the response of KPM PKH in Nagari Gunuang Rajo in terms of perception, attitude and participation aspects showed a positive response where each had a value of 0.89 for perception, 0.83 for attitude, and 0.85 for participation. This can be seen from the PKH KPM who have understood the purpose of changing the PKH program assistance scheme as well as the terms, methods and times of distributing aid and actively participating in PKH activities.